Gender and the modern organization, ten years after - Abrahamsson, Lena (Nordic Journal of Working Life Studies, 2015)
This empirical article presents a gender analysis of long-term impacts of some of the many organizational change projects in Swedish industrial work organizations during the 1990s. Based on the results of return visits to three industrial companies and their change projects (implementation of Lean Production or other modern organizational models) that I studied more than a decade earlier, I discuss how the work organizations eventually had changed and specifically how and whether organizational internal gender patterns had changed. The initial study showed genderbased restoring responses to strategic organizational changes, especially in the gender-segregated and gender-homogeneous work organizations. These responses conserved gender patterns as well as the organizations’ culture in general, resulting in less productive work as well as a problematic work environment. The follow-up study showed that the organizations slowly changed according to the modern organizational models (e.g., Lean Production), but at the same time, in some cases, keeping the same gender segregation and stereotypical gender markings of skills and work tasks or with new variants of unequal gender order. In addition, the follow-up study showed other and more positive results with emerging pattern of gender equality, at least in the form of reduced gender segregation and less stereotypical ideas concerning gender. The material indicates that the studied companies, in some aspects, developed into less gendered production organizations while taking some steps toward a modern organization and this was done without gender equality interventions. Therefore, the material indicated that, at least in part, gender equality could be seen as a prerequisite or perhaps even a side effect of modern organizational concepts. This article contributes to the emerging literature on an organizational theory of undoing gender as well as to the research of conditions and consequences of the modern organizational models.